Integrated Farming Systems Approach for Income Enhancement and Employment Generation in North-West India - Singh, Ravinder; Riar , T. S. (Indian Journal of Extension Education, 2014)
Astudy was conducted during 2011-12 in Punjab to find out the productivity, profitability and employment generation of  integrated farming system as compared to conventional cropping system. The study comprised of two integrated farming  systems viz., crop + floriculture and crop + bee-keeping. Both these integrated farming systems were productive and  profitable than that of sole cropping system. The net returns increased in the tune of 29.53 per cent and 19.09 per cent per  hectare with inclusion of floriculture and bee-keeping enterprises, respectively over sole cropping system. The study also  indicated that crop + floriculture farming system generated 31.03 mandays/hectare/annum/farm employment for family,  46.14 mandays/hectare/annum/farm for hired labour and 77.17 mandays/hectare/annum/farm as total labour. In case of  crop + bee-keeping, it was observed that employment generated through crop + bee-keeping farming system for family  labour was 29.61 mandays/hectare/annum/farm, for hired labour was 40.12 mandays/hectare/annum/farm and for total  labour was 69.73 mandays/hectare/annum/farm.
Keywords: Integrated farming systems; income enhancement; employment generation